The Nexus Between Maqasid al Sharia and affordable housing program in Indonesia: A systematic review of legal regulations - Muhammad Abdul ghoni; Muhammad Taufik Affandi (Tathawwur: Jurnal Ekonomi Pembangunan dan Keuangan Islam, 2025)
The affordable housing can be defined as housing for low-income people (MBR), who have limited ability to obtain housing and supported by government of Indonesia within the financing program throughout Islamic banking as stated in the Minister of Public Works and Public Housing Regulation Number 1 of 2021 on criteria for low-income people (MBR), easy requirements to build and own a house. This emphasizes the importance of affordable housing for low-income people is to promote the welfare of the people that in accordance to the objectives of the Shariah (Maqasid al Sharia). The current study examines the nexus between Maqasid al Sharia and legal regulation of republic Indonesia as the basis of affordable housing program. To explore and optimize the harmonization the objectives of the Shariah (Maqasid al Sharia) and legal regulation of republic Indonesia, we analyze the legal regulations contents of republic Indonesia to expose the indicators and spirits of the objectives of the Shariah (Maqasid al Sharia) in the affordable housing programs. Using Systematic review tool, these indications and spirit of the objectives of the Shariah (Maqasid al Sharia) are identified on the basis reviewed and analysis of legal regulation. A systematic study results show that, the indicators, and spirits of the Maqasid al Sharia; protection of religion (din), protection of life (Nafs), protection of intellect (Aql), protection of wealth (Mal), and protection of lineage (Nasl) are reflected in the legal regulation of Republic of Indonesia as groundbreaking affordable housing program.